EFEKTIVITAS KINERJA BADAN USAHA MILIK DESA TERHADAP PEMBERDAYAAN USAHA MIKROKECIL DAN MENENGAH DI DESA AKA-AKAE KECAMATAN WATANG SIDENRENG KABUPATEN SIDENRENG RAPPANG - Ika Fiqria; Erfina Erfina; Andi Astinah Adnan (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
The purpose of this research is to determine the Effectiveness of the Performance of Village-Owned Enterprises on Empowerment of Micro, Small and Medium Enterprises in Aka-Akae Village, Watang Sidenreng District, Sidenreng Rappang Regency, the data analysis technique used is descriptive statistics using data collection techniques including observation, interviews , and a questionnaire. The population in this study were 1,519 people and the sampling used was probability sampling with a random sampling technique in order to obtain a sample of 76 people. Data analysis was performed with the help of the SPSS 16.0 program. The results of this study indicate that the effectiveness of the performance of Village-Owned Enterprises is at a percentage of 64.6% or is in the good category, while the empowerment of Micro, Small and Medium Enterprises is at a percentage of 62.4% or is in the good category. The effectiveness of the performance of Village-Owned Enterprises in Aka-Akae Village has a significant effect on the empowerment of Micro, Small and Medium Enterprises with a value of t count ≥ t table (4.021> 1.66571) and a percentage of 17.9%.